Structural Effects of Regional Reproduction and Supply Chain Strategy in Russia: Impact on Market and Administrative Coordination Relationship - Miropolskii D.Iu.; Borkova E.A.; Vatlina L.V.; Kapelyuk Z.A. (International Journal of Supply Chain Management, 2019)
Abstract-This article is a continuation of a previously published study devoted to the interaction analysis of the national and regional economies through a two-sector model [1]. The concept is based on the proportion between the resource-rich and resource-poor sectors. In the previous article, we showed the fundamental possibility of using this two-sector model for the study of regional economy. In continuation of our study, we will use the two-sector model to study the interrelationships of individual regions using possible situations with different proportions of the resource-rich and resource-poor sectors. Although the two-sector model is initially based on the fundamentally different theoretical grounds, the practical conclusions from this model do not contradict the neoclassical theory of regional development. It is shown how government regulation can help or hinder the development of a separate region, as well as influence the degree of uneven economic development of the regions.